Proton pump inhibitor has no effect in the prevention of post-endoscopic sphincterotomy delayed bleeding: a prospective randomized controlled trial - Yu, Zhengping; He, Jinli; Cao, Ronglai; Yang, Zhenzhen; Li, Baolian; Hong, Junbo; Chen, Youxiang; Zhu, Liang (Frontiers in Medicine, 2023)
Background and Aims: Bleeding is one of the common adverse events of endoscopic retrograde cholangiopancreatography (ERCP), which is mainly caused by endoscopic sphincterotomy (EST). At present, it remains unclear whether proton pump inhibitor (PPI) should be used to prevent post-EST bleeding. Therefore, we performed a randomized controlled trial to investigate whether PPI is effective in the prevention of post-EST delayed bleeding. Methods: Consecutive eligible patients were randomly assigned (1:1) to experimental group (PPI group) or control group (normal saline, NS group). The patients in PPI group received intravenous esomeprazole 40mg and normal saline 100ml every 12 hours for 2 days after ERCP immediately, and followed by oral esomeprazole (Nexium) 20mg once a day for 7 days. Correspondingly, patients in the control group received intravenous normal saline 100 ml and didn’t take PPIs or any acid-suppressing drugs during hospitalization and after discharge. All patients were followed up for 30 days after ERCP. The primary endpoint was the incidence and severity of post-EST delayed bleeding. Results: Between July 2020 and July 2022, 290 patients were randomly assigned to PPI group (n=146) or NS group(n=144). 5 patients from each group were excluded from the final analysis. There were 6 patients with post-EST delayed bleeding, with an incidence rate of 2.14%. The median time of delayed bleeding was 2.5 days after ERCP. 3 cases (2.12%, 3/141) occurred in the PPI group, with 1 case of mild and 2 cases of moderate bleeding. 3 cases (2.16%, 3/139) occurred in the NS group, with 2 cases of mild and 1 case of moderate bleeding. There was no significant difference in the incidence and the severity of post-EST delayed bleeding between the two groups (P=1.000). Conclusion: Prophylactic use of PPI after EST does not reduce the incidence and severity of post-EST delayed bleeding in patients.